Sexualidade de mulheres com deficiência adquirida : enfermagem na promoção da saúde e empoderamento - Baptista, Rosilene Santos (2011)
Sexuality is defined as a central feature of human beings which is part of their whole existence. Everybody has the right to explore its sexuality, however, there are difficulties imposed to disabled women. We live in a society which emphasizes the beauty and perfection, so that those who are not framed to this stereotype become stigmatized. Hence, this thesis aims to investigate and promote the sexuality of disabled women. Its main objective is to intermediate the disabled women empowerment so that they can explore their sexuality more pleasantly. We did our study using qualitative analysis, in a group of six disabled women, from June to October of 2010. The group investigated is part of the Campina Grande Disabled Association (ASDECB), located in Campina Grande – PB, Brazil. During this research we took into account the Brazilian Resolution 196/96 which focuses on research involving human beings. The data gathering process involved questionnaires; interviews; audio recording; and observations registered in a logbook. Focal group methodology was used during ten sessions. After that, data were analyzed and categorized through thematic analysis, using as a theoretical reference the health promotion in the empowerment perspective. We obtained three categories: conception, sexuality promotion and empowerment, and their subcategories respectively. As a result, women proved to be disempowered as to the exercise of their sexuality; the family, in majority, did not contribute to a healthy sexuality and also the health professionals shown not able to deal with sexuality aspects; the main challenges mentioned by the women were to overcome the prejudice and the fear to be sexually abused. As a conclusion, we point out that although the empowerment be a long term process, it can be built through actions on health promotion that seek for criticism and reflection of people involved, so that a pleasant, healthy and empowerment sexuality may be achieved.